International Spill-Over of Technologies and Regional Agglomeration and Development - Gries, Thomas (Science Research Management)

Obstacles Facing German Enterprises in South Africa - Gilroy, Bernard Michael; Gries, Thomas; Naudé, Willem A.; Schmidt, K.-H. (Multinational Enterprises, Foreign Direct Investment and Growth in Africa: South African Perspectives)

The effects of epistemological beliefs on workplace learning - Bauer, Johannes; Festner, Dagmar; Gruber, Hans; Harteis, Christian; Heid, Helmut (Journal of Workplace Learning)

Competence-supporting working conditions - Harteis, Christian; Gruber, Hans (Professional learning: Gaps and transitions on the way from novice to expert)

Zur Vereinbarkeit ökonomischer und pädagogischer Prinzipien in der modernen betrieblichen Personal-und Organisationsentwicklung - Heid, Helmut; Harteis, Christian (Zeitschrift für Berufs-und Wirtschaftspädagogik, Beiheft)

Wissensmanagement und Expertise - Gruber, Hans; Harteis, Christian; Rehrl, Monika (Psychologie des Wissensmanagements. Perspektiven, Theorien und Methoden)

Zur Diskussion über die Konvergenz ökonomischer und pädagogischer Prinzipien betrieblicher Personal-und Organisationsentwicklung - Harteis, Christian (Zeitschrift für Erziehungswissenschaft)

Self-determination in daily working life - Harteis, Christian; Bauer, Johannes; Festner, Dagmar; Gruber, Hans (Current issues in adult learning and motivation. 7th Adult Education Colloquium)

The learning organisation as seen by workers - Harteis, Christian (VOCATIONAL TRAINING-BERLIN-CEDEFOP-)

Kapital und Kompetenz: Veränderungen in der Arbeitswelt und ihre Auswirkungen aus erziehungswissenschaftlicher Sicht

Selbstbestimmung im Arbeitsalltag - Harteis, Christian; Bauer, Johannes; Festner, Dagmar; Gruber, Hans (UNTERRICHTSWISSENSCHAFT.)

Fehlerorientierung im betrieblichen Arbeitsalltag. Ein Vergleich zwischen Führungskräften und Beschäftigten ohne Führungsfunktion - Bauer, Johannes; Festner, Dagmar; Harteis, Christian; Heid, Helmut; Gruber, Hans (Zeitschrift für Berufs-und Wirtschaftspädagogik)

Förderung und Anwendung individueller Kompetenz im Arbeitsalltag - Harteis, Christian; Festner, Dagmar (Kapital und Kompetenz)

Betriebliche Personal-und Organisationsentwicklung zwischen ökonomischen und pädagogischen Überlegungen - Harteis, Christian; Bauer, Johannes; Coester, Helene (Kapital und Kompetenz)

Betriebliche Personal- und Organisationsentwickllung zwischen ökonomischen und pädagogischen Überlegungen - Harteis, Christian; Bauer, Johannes; Coester, Helene (Kapital und Kompetenz: Veränderungen der Arbeitswelt und ihre Auswirkungen aus erziehungswissenschaftlicher Sicht)

Provably Secure Masking of AES - Blömer, Johannes; Guajardo, Jorge; Krummel, Volker (Selected Areas in Cryptography)

A Generalized Wiener Attack on RSA - Blömer, Johannes; May, Alexander (Public Key Cryptography – PKC 2004)

Secret Exponent Attacks on RSA-type Schemes with Moduli N=p^{r}q - May, Alexander (Public Key Cryptography – PKC 2004)

Computing the RSA Secret Key Is Deterministic Polynomial Time Equivalent to Factoring - May, Alexander (Advances in Cryptology – CRYPTO 2004)

A new CRT-RSA algorithm secure against bellcore attacks - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Proceedings of the 10th ACM conference on Computer and communication security - CCS '03)

Interbank market frictions, international banks and growth - Gries, Thomas; Sievert, Gerhard; Wieneke, Axel (International Economics and Economic Policy)

Anreizkompatibilität als zentrales Element eines neu gestalteten Gesundheitsmarktes - Gries, Thomas; Langeleh, Dirk (Perspektiven der Wirtschaftspolitik)

Traffic and Hop Efficient Position-based Routing using a Cell Structure - Rührup, Stefan; Schindelhauer, Christian

Differences between recumbent length and stature measurement in groups of 2- and 3-y-old children and its relevance for the use of European body mass index references - Buyken, Anette; Hahn, S; Kroke, A (International Journal of Obesity)

Verbraucherbildung im Forschungsprojekt REVIS – Grundlagen - Schlegel-Matthies, Kirsten

„Was gibt’s heute?“ Aktuelle Ansätze der Ernährungsbildung - Schlegel-Matthies, Kirsten (Campus Culinaire)

User-driven adaption in rule-based pattern recognition - Niere, Jörrg; Meyer, Matthias; Wendehals, Lothar
Today, in software intensive projects a huge amount of the budget flows into the analysis of the already existing system. The reason for the high costs results mainly from the fact that analyses are often made manually or with automatic tool support, which is inappropriate for analyzing large systems. Semi-automatic analysis approaches usually use a notion of fuzziness to overcome this limitation, but inherit the problem of selecting appropriate initial values. In this paper we present an approach to adapt the initial values of our semi-automatic reverse engineering process. We provide the reverse engineer with accuracy information for results produced by a rule-based inference algorithm. Based on the changes of the results done by the reverse engineer we automatically adapt a credibility value of each rule, which previously has been used to compute the accuracy of the result. The adaption fits seamlessly into our overall analysis process. First tests show that it is suitable for the calibration of our fuzzyfied rule-based pattern recognition approach.

Kleben von CFK-Metall-Strukturen im Fahrzeug - Meschut, Gerson; Fuhrmann, T. (Tagungsband zum 4. Kolloquium „Gemeinsame Forschung in der Klebtechnik“ der DECHEMA)

Forschungsbedarf in der Klebtechnik aus Sicht der Automobilindustrie - Meschut, Gerson

Adhesive bonding and mechanical joining for planking of spaceframe-structures with thermoplastics - Bischof, S.; Fricke, A.; Meschut, Gerson (Tagungsband zur Swiss Bondung ´04)

New material and design concepts for constructions of vehicles – challenges for thermal an cold joining techniques - Meschut, Gerson; Goede, M. (Tagungsband zur 9. International Aachen Welding Conference: Joining in Traffic and Transportation Industry – Processes, Progress, Applications)

Kleben und Hybridfügen von Leichtbaustrukturen für den Automobilbau - Disse, T.; Maciej, M.; Meschut, Gerson; Piccolo, S.; Timmermann, R.; Wibbeke, T.-M. (Adhäsion)

Mechanische Fügetechnik für die Mischbauweise – Teil 1: Systemoptimierungen - Letsch, S.; Meschut, Gerson; Küting, J.; Peitz, V.; Timmermann, R.; Schmid, L. (Schweißen und Schneiden)

Material-Secific joining techniques for magnesium body structures - Hahn, O.; Schumann, S.; Meschut, Gerson; Fuhrmann, T.

Mechanische Fügetechnik für die Mischbauweise – Teil 2: Neuartige Fügeverfahren - Letsch, S.; Meschut, Gerson; Küting, J.; Peitz, V.; Timmermann, R.; Schmid, L. (Schweißen und Schneiden)

Simple On-Line Algorithms for the Maximum Disjoint Paths Problem - Kolman, Petr; Scheideler, Christian (Algorithmica)

Group Spreading: A Protocol for Provably Secure Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (ICALP)

A Distributed Hash Table for Computational Grids - Riley, Chris; Scheideler, Christian (IPDPS)

Zukünftige Werkstoff- und Bauweisenkonzepte im Automobilbau - Herausforderungen für die Gewindetechnologie - Meschut, Gerson (Tagungsband zum 2. Böllhoff-Fachkolloquium)

Fügen von Kunststoffen im strukturellen Leichtbau - Bye, C.; Draht, T.; Küting, J.; Lübbers, R.; Meschut, Gerson; Ruther, M. (Tagungsband zum 11. Paderborner Symposium Fügetechnik „Mechanisches Fügen und Kleben“)

Robust Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (IPTPS)

Druckfügeverfahren und damit hergestellte Rahmen - Hahn, O.; Meschut, Gerson

Fügeverfahren und Fügevorrichtung zum Verbinden von überlappend angeordneten Fügeteilen - Amedick, Jürgen; Hahn, Ortwin; Kurzok, Jan; Letsch, Stefan; Meschut, Gerson; Peitz, Volker; Timmermann, Rüdiger

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IWIA)

The hyperring: a low-congestion deterministic data structure for distributed environments - Awerbuch, Baruch; Scheideler, Christian (SODA)

Consistent and compact data management in distributed storage systems - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Pagoda: a dynamic overlay network for routing, data management, and multicasting - Bhargava, Ankur; Kothapalli, Kishore; Riley, Chris; Scheideler, Christian; Thober, Mark (SPAA)

The effect of faults on network expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (SPAA)

math-kit - Ein multimedialer Baukasten für die Mathematikausbildung im Grundstudium - Unger, L.; Bauch, M.; Baudry, A.; Bungenstock, M.; Mertsching, B.; Oevel, Gudrun; Padberg, K.; Thiere, B. (SoftwareTechnikTrends)

V:Drive - Costs and Benefits of an Out-of-Band Storage Virtualization System - Brinkmann, André; Heidebuer, Michael; Meyer auf der Heide, Friedhelm; Rückert, Ulrich; Salzwedel, Kay; Vodisek, Mario (21st IEEE Conference on Mass Storage Systems and Technologies / 12th NASA Goddard Conference on Mass Storage Systems and Technologies, Greenbelt, Maryland, USA)